REVIEW ARTIKEL: KADAR FLAVONOID EKSTRAK ETANOL DAUN DARI BEBERAPA JENIS TANAMAN - Jannah, Miftahul (Makassar Natural Product Journal (MNPJ), 2024)
Flavonoids are one of the compounds that can be obtained from nature that has been widely used by the community. Flavonoids are one of the classes of secondary metabolites produced by plants that belong to a large group of polyphenols, these compounds are found in all parts of the plant including leaves. The solvent used in this study was ethanol. The purpose of this article review is to determine the flavonoid levels of ethanol extract leaves from several types of plants. The method used in this study is a narrative review based on inclusion and exclusion criteria. The results of this study flavonoid levels of ethanol extract from the leaves of several types of plants, the highest of which were flavonoid levels of Moringa leaf ethanol extract (Moringa oleifera L.) amounted to 94.1842 mg QE gr extract. The presence of flavonoid compounds in Moringa leaves can be an alternative to be used as herbal medicine in healing various diseases.